Professional Identity Formation in a Global Socio-Environmental Crisis - Cuadra Martínez, David (2021)
Background: we are facing a global crisis that threatens the subsistence of the planet. Although during the last decades a set of measures have been proposed to face this global crisis, the results have not been auspicious. State of the art: given the important role of professionals in society, in this work it is argued that a systematic development of professional identity in initial training is key to sustainable development. It is proposed that this professional identity could be built based on the dimensions (a) integration of subjective, professional and scientific knowledge, (b) creativity to address current and future problems, (c) prosocial and (d) ecological. The objective of this work is to support the urgency of this to respond to the global crisis and provide suggestions that guide the systematic development of professional identity during initial training, based on these dimensions. Conclusions: from the scientific literature, the need to systematically form the professional identity based on these dimensions is argued, providing suggestions in this regard. Author Contribution DC-M: preparation of the manuscript. PC-C: revision of the manuscript, general writing and support in the literature search. COV: general revision of the article and support in the elaboration of the conclusion. IG-P: general revision of the article and support in the development of the article. JSD: general revision of the article and support in the elaboration of the introduction of the article.